What is precise pathophysiology in development of hypertension in pregnancy? Precision medicine requires precise physiology and pathophysiology. Issue 2 (February 2018) - Gao, Qinqin; Tang, Jiaqi; Li, Na; Liu, Bailin; Zhang, Mengshu; Sun, Miao; Xu, Zhice
Highlights: Placental ischemia could be the key in the evolution of processing PH. Special physiology of placental vascular systems should be fully investigated. Placental vascular dysfunction is associated with preeclamptic conditions. This review provides new clue and ideas for the mechanisms and treatments of PH. Abstract : It is widely accepted that placental ischemia is central in the evolution of hypertension in pregnancy. Many studies and reviews have targeted placental ischemia to explain mechanisms for initiating pregnancy hypertension. The placenta is rich in blood vessels, which are the basis for developing placental ischemia. However, is the physiology of placental vessels the same as that of nonplacental vessels? What is the pathophysiology of placental vessels in development of pregnancy hypertension? This review aims to provide a comprehensive summary of special features of placental vascular regulations and the pathophysiological changes linked to preeclamptic conditions. Interestingly, some popular theories or accepted concepts could be based on our limited knowledge and evidence regarding placental vascular physiology, pharmacology and pathophysiology. New views raised could offer interesting ideas for future investigation of mechanisms as well as targets for pregnancy hypertension. Teaser: Special physiology and precise pathophysiology in placental vessels are crucial in understanding mechanisms of pregnant hypertension and the basis for precision medicine targeting preeclampsia.